Dry sliding wear behavior of aluminum graphene nanoplatelet (GNP) composites - Istif, Ilyas; Tuncel, Mehmet Tunc (CARL HANSER VERLAG, 2016)
Conventional aluminum (Al) and its alloys have been replaced by aluminum matrix composites (AMCs) due to their superior properties in the recent years. There are several attractive candidates as reinforcement for aluminum composites such as Al2O3, B4C and SiC. Nowadays, carbon based materials such as graphite, carbon nanotubes (CNTs) and graphene have attracted much attention owing to their above mentioned mechanical and physical properties. In this study, the wear behavior of Al graphene nanoplatelets (GNPs) composites reinforced with up to 2 wt.-% GNP were investigated. The addition of graphene up to 1 wt.-% decreased coefficient of friction. Experimental data were used to develop linear and nonlinear models. The experimental results are in good agreement with the results of the simulations based on the identified models.
Keywords: Wear behavior; powder metallurgy; metal matrix composite; modeling; PREDICTION; Materials Science